The genre repertoires of Norwegian beauty and lifestyle influencers on YouTube - Torjesen Aleksander (Nordicom Review, 2021)
YouTube represents an increasingly popular cultural phenomenon in the contemporary Norwegian media landscape. Since the inception of the digital video platform over 15 years ago, personal videoblogging has emerged as one of its dominant types of user-generated content. In this article, I draw from New Rhetoric genre theory and netnographic approaches to explore the beauty and lifestyle sphere on YouTube, in which several emergent genres are situated within a new media ecosystem. Through a qualitative content analysis of seven established Norwegian YouTube channels, a total of 17 individual genres were identified. Furthermore, I elaborate upon how informational, instructional, and confessional communicative functions are utilised in audiovisual publications through conventionalised digital media production practices.